Heritage buildings towards the future: conservation and circular economy for sustainable development - Antonini, Ernesto; Favaretto, Giulia; Pretelli, Marco (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The issues of energy efficiency and climate change belong to a complex scenario to which contemporaneity is called upon to answer. Architecture can contribute by promoting practices that look at the environment with a view to building the future. As an architectural activity, restoration of heritage buildings can actively participate in this fundamental challenge within the perspective of a circular economy proposing a globally sustainable model. Starting from a state-of-the-art investigation, this paper aims to enucleate the BECK project’s contribution in this field, as well as to underline how careful strategies of conservation and contemporary use can have positive effects on sustainable future scenarios.